2021
DOI: 10.1002/pon.5697
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and stress in women with suspected endometrial cancer: Survey and paired observational study

Abstract: Objective To determine the anxiety and stress levels of women with suspected endometrial cancer and factors affecting this. Methods Prospective survey and paired observational study of consecutive women with suspected endometrial cancer in a rapid access gynaecology clinic. Structured questionnaire including a GAD‐7 anxiety test and a modified stress thermometer were used. Patients ranked their perception of a cancer diagnosis on 0‐5 Likert scale (0 = confident not cancer and 5 = cancer). Patients requiring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Histological diagnosis can take up to two weeks. It has been demonstrated that delays in diagnosis are associated with high levels of anxiety and stress for patients [ 2 , 3 , 4 , 5 , 6 ]. The mainstay of treatment for endometrial cancer is hysterectomy, with large international observational studies showing that delays to definitive surgery can negatively impact survival [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histological diagnosis can take up to two weeks. It has been demonstrated that delays in diagnosis are associated with high levels of anxiety and stress for patients [ 2 , 3 , 4 , 5 , 6 ]. The mainstay of treatment for endometrial cancer is hysterectomy, with large international observational studies showing that delays to definitive surgery can negatively impact survival [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many kinds of cancer patients, the anxiety level of female patients is signi cantly higher than that of male patients, and gynecological cancer patients are one of the highest anxiety groups [9,10]. Studies have shown that the incidence of anxiety in gynecologic cancer patients is 23.7-42% [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out in 2007 by Nielsen and colleagues, a weak correlation between stress and EC was found in the severely stressed group; in fact, a lower risk of EC was observed among stressed women [ 264 ]. Due to the small, sampled population ( n = 72), several research studies have focused on a much larger and diverse sampling method [ 265 , 266 ], and a study of 250 patients and multiple races/ethnicities found out that stress played a key role in the development of EC [ 265 ].…”
Section: Discussionmentioning
confidence: 99%